Cancer incidence in Italian contaminated sites - Pietro Comba; Paolo Ricci; Ivano Iavarone; Roberta Pirastu; Carlotta Buzzoni; Mario Fusco; Stefano Ferretti; Lucia Fazzo; Roberto Pasetto; Amerigo Zona; Emanuele Crocetti (Istituto Superiore di Sanità, 2014)
INTRODUCTION. The incidence of cancer among residents in sites contaminated by pollutants with a possible health impact is not adequately studied. In Italy, SENTIERI Project (Epidemiological study of residents in National Priority Contaminated Sites, NPCSs) was implemented to study major health outcomes for residents in 44 NPCSs. METHODS. The Italian Association of Cancer Registries (AIRTUM) records cancer incidence in 23 NPCSs. For each NPCSs, the incidence of all malignant cancers combined and 35 cancer sites (coded according to ICD-10), was analysed (1996-2005). The observed cases were compared to the expected based on age (5-year period,18 classes), gender, calendar period (1996-2000; 2001-2005), geographical area (North-Centre and Centre-South) and cancer sites specific rates. Standardized Incidence Ratios (SIR) with 90% Confidence Intervals were computed. RESULTS. In both genders an excess was observed for overall cancer incidence (9% in men and 7% in women) as well as for specific cancer sites (colon and rectum, liver, gallbladder, pancreas, lung, skin melanoma, bladder and Non Hodgkin lymphoma). Deficits were observed for gastric cancer in both genders, chronic lymphoid leukemia (men), malignant thyroid neoplasms, corpus uteri and connective and soft-tissue tumours and sarcomas (women). DISCUSSION. This report is, to our knowledge, the first one on cancer risk of residents in NPCSs. The study, although not aiming to estimate the cancer burden attributable to the environment as compared to occupation or life-style, supports the credibility of an etiologic role of environmental exposures in contaminated sites. Ongoing analyses focus on the interpretation of risk factors for excesses of specific cancer types overall and in specific NPCSs in relation to the presence of carcinogenic pollutants.